2007
DOI: 10.1097/01.hp.0000252259.72683.2a
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Risk Associated to Exposure to Radon and Smoking in a Case-Control Study of French Uranium Miners

Abstract: A case-control study nested in the cohort of French uranium miners took smoking information into account in investigating the effect of radon exposure on lung cancer risk. This study included 100 miners who died of lung cancer and 500 controls matched for birth period and attained age. Data about radon exposure came from the cohort study, and smoking information was retrospectively determined from a questionnaire and occupational medical records. Smoking status (never vs. ever) was reconstructed for 62 cases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 27 publications
1
46
1
Order By: Relevance
“…However, a significant increase in the ERR per 100 WLM was noted with increasing number of cigarettes smoked daily (Villeneuve et al, 2007). In a recent French nested case-control study, the ERR for lung cancer related to cumulative radon exposure, adjusted for smoking, was 0.85 per 100 WLM (Leuraud et al, 2007). Adjustment for smoking only led to marginal changes in the risk of lung cancer associated with radon (Leuraud et al, 2007;Schnelzer et al, 2010).…”
Section: Influence Of Possible Modifying Factorsmentioning
confidence: 96%
“…However, a significant increase in the ERR per 100 WLM was noted with increasing number of cigarettes smoked daily (Villeneuve et al, 2007). In a recent French nested case-control study, the ERR for lung cancer related to cumulative radon exposure, adjusted for smoking, was 0.85 per 100 WLM (Leuraud et al, 2007). Adjustment for smoking only led to marginal changes in the risk of lung cancer associated with radon (Leuraud et al, 2007;Schnelzer et al, 2010).…”
Section: Influence Of Possible Modifying Factorsmentioning
confidence: 96%
“…With respect to potential confounders, information on smoking habits for subgroups of the three cohorts was collected from nested case-control studies on lung cancer (Leuraud et al, 2007;Schnelzer et al, 2010;Leuraud et al, 2011;Tomasek, 2011). Additional information on potential occupational confounders (e.g.…”
Section: Epidemiological Issuesmentioning
confidence: 99%
“…74 Studies of French uranium miners report an excess 0.71-0.85% risk for lung cancer per 100 working level months. 75,76 Another study reported that uranium miners lose on average of 1.5 years of potential life because of mining related lung cancer or 3 months of life for each year employed as a uranium miner. 77 As with other miners, lung cancer is reportedly the only cancer found to be consistently associated with uranium-mining occupational exposures, and higher radiation exposure tends to increase the relative frequency of squamous cell and small cell lung cancer.…”
Section: Estimation Of Health Risksmentioning
confidence: 99%